Design of a Device for Optimizing Burden Distribution in a Blast Furnace Hopper - Gabriele Degrassi; Lucia Parussini; Marco Boscolo; Elio Padoano; Carlo Poloni; Nicola Petronelli; Vincenzo Dimastromatteo (Information)
The coke and ore are stacked alternately in layers inside the blast furnace. The capability of the charging system to distribute them in the desired manner and with optimum strata thickness is crucial for the efficiency and high-performance operation of the blast furnace itself. The objective of this work is the optimization of the charging equipment of a specific blast furnace. This blast furnace consists of a hopper, a single bell and a deflector inserted in the hopper under the conveyor belt. The focus is the search for a deflector geometry capable of distributing the material as evenly as possible in the hopper in order to ensure the effective disposal of the material released in the blast furnace. This search was performed by coupling the discrete element method with a multi-strategy and self-adapting optimization algorithm. The numerical results were qualitatively validated with a laboratory-scale model. Low cost and the simplicity of operation and maintenance are the strengths of the proposed charging system. Moreover, the methodological approach can be extended to other applications and contexts, such as chemical, pharmaceutical and food processing industries. This is especially true when complex material release conditions necessitate achieving bulk material distribution requirements in containers, silos, hoppers or similar components.